Implication of human attitude factors toward information security: awareness in Malaysia Public University - Ahlan, Abdul Rahman; Arshad, Yusri; Lubis, Muharman (2011)
Without a doubt, the whole world faces many challenges regarding hacker or cracker exploitation; and spammer in various sector such as Internet security, software privacy, email, etc. While Malaysian government attempted to establish several cyber laws in order to encounter the problem, mainly as the guidance for technology user’s purpose, the danger in information exploitation still arise. The important factor that supports the successful of these policies implementation resides on how to raise the awareness among community. This process will give significance contribution to the effectiveness of policy implementation by its continuity through the communication chain and regularly information distribution. Government can’t overrule the importance of university policies in building the awareness among student at beginning phase. Therefore, some factors need to be identified first, from which level that might influence positively the awareness in university. It has the function to measure the level of awareness for the improvement and performance purpose. However, the problem will always occur in terms of evolving the human mind in utilizing technology services, which put information security susceptible to attack and there is no standard regulation to ensure that human attitude involved delivering the secure and safety result. So, we can conclude that human error could be as greatest risk if current organization’s policy doesn’t have the capability to control and manage it accordingly and frequently.